Methods of Therapy and Rehabilitation of Drug Victims in Bidayatussalikin Islamic Boarding School - Wayoi, Deny Setiawan (Program Pascasarjana Universitas Negeri Yogyakarta, 2024)
The abuse of narcotics, psychotropic substances, and addictive substances in Indonesia, especially in the Special Region of Yogyakarta (DIY), has reached an alarming level. According to data from the National Narcotics Agency (BNN), the number of cases and the seizure of narcotics evidence in DIY shows significant fluctuations each year, with the majority of abuse victims being male students aged 15-64 years. Bidayatussalikin Islamic Boarding School plays an important role in assisting teenagers who are victims of narcotics abuse in DIY. This research aims to identify the therapy and rehabilitation methods implemented by Bidayatussalikin Islamic Boarding School for these victims. The approach used is descriptive qualitative, involving musyrif, counselors, and students as research subjects. The results indicate that the Sufi approach, including takhalli (self-cleansing), tahalli (self-filling), and tajalli (self-control development), is applied as a therapy and rehabilitation method, and has proven to have a positive impact on former students who are victims of narcotics abuse, both physically, psychologically, and psychomotorically. This success is also supported by community participation and cooperation with government agencies. This research contributes by highlighting the importance of a spiritual approach in the rehabilitation of narcotics abuse victims and the role of Islamic boarding schools as effective rehabilitation centers